A Leadership Capability Framework for Supporting Strategic Transformation and Employee Engagement: A Case Study in an Aerostructure Strategic Business Unit - Dhilal Ahmad Sobarudin; Aurik Gustomo (PT. Hasba Edukasi Mandiri, 2025)
Amid its ongoing strategic transformation, the Aerostructure Strategic Business Unit (SBU) of XYZ Company, a pseudonym for an Indonesian aerospace company, faces the challenge of aligning leadership practices with its transformation goals and enhancing employee engagement. While corporate-level assessments indicated leadership and engagement challenges across the organization, no systematic analysis had previously been conducted at the SBU level, nor had a leadership framework been specifically developed to address these needs. This study developed a Strategic Leadership Capability Framework (SLCF-Aero), synthesized from established leadership capability literature and tailored to the dynamic leadership practices emerging during the SBU’s transformation and employee engagement efforts. The framework’s relevance and impact were explored through empirical analysis of employee perceptions and engagement outcomes, using Partial Least Squares (PLS-SEM) on survey data from 42 employees. The findings reveal varied employee perceptions of leadership practices across the SLCF-Aero domains. Notably, only the People-First Orientation exhibited a statistically significant positive relationship with employee engagement. Nevertheless, the overall framework provides a relevant foundation for guiding leadership practice development within the SBU and supporting its transformation and engagement objectives. Moreover, it highlights the potential for such frameworks to inform leadership learning and the evolving practice of leadership within organizational change contexts.